07.08 Contribution of mthfr gene polymorphisms in primary sjögren's syndrome related lymphomagenesis. (1st March 2017) - Fragkioudaki, Sofia; Nezos, Adrianos; Saetta, Aggeliki A; Drakoulis, Nikolaos; Souliotis, Vasilis L; Sfikakis, Petros P; Tzioufas, Athanasios G.; Voulgarelis, Michael; Koutsilieris, Michael; Crow, Mary K; Moutsopoulos, Haralampos M; Mavragani, Clio P
Abstract : Background: Among systemic autoimmune disorders, primary Sjogren's syndrome (pSS) has the highest risk for non-Hodgkin lymphoma (NHL) development. Two common polymorphisms, the C677T and A1298C, of the methylene-tetrahydrofolate reductase (MTHFR) gene, an enzyme essential in DNA synthesis, repair and methylation, have been reported to influence susceptibility to both autoimmune diseases and NHL. The aim of this study was to investigate the possible contribution of MTHFR variants in pSS-related lymphomagenesis. Materials and methods: 262 pSS patients without NHL (pSS), 94 pSS patients with NHL [pSS-lymphoma, of which 75 had mucosa-associated lymphoid tissue (MALT) and 19 non-MALT] as well as 600 healthy controls (HC) of similar age and sex distribution were genotyped by PCR-based assays for the detection of the MTHFR gene polymorphisms (C677T and A1298C). To further evaluate the functional consequences of MTHFR variants, global DNA methylation levels were assessed by bisulphite pyrosequencing of the LINE-1 retroelement promoter in genomic DNA derived from 55 salivary gland tissues from pSS patients. Additionally, DNA double strand breaks -a marker of intrinsic DNA damage as a result of defective DNA repair- were determined in peripheral blood mononuclear cells isolated from 13 pSS patients, using comet assay. Results: The frequency of MTHFR polymorphisms did not differ among pSS, pSS-lymphoma patients and HC. However, further data analysis according to the lymphoma subtype revealed increased frequency of C677T TT genotype and T allele in the pSS non-MALT group compared to pSS patients [OR(95% CI): 2.13 (1.06–4.30), p=0.03] and HC [OR(95% CI): 1.93 (1.01–3.68), p=0.04], respectively. On the other hand, the prevalence of the A1298C C allele was reduced among pSS non-MALT individuals compared to both pSS patients [OR(95% CI): 0.29 (0.10–0.83), p=0.01] and HC [OR(95% CI): 0.25 (0.09–0.70), p=0.004]. Of interest, MTHFR C677T TT genotype was associated with reduced global DNA methylation levels (TT vs CC: 71.57±5.43 vs 75.56±4.13, p=0.045), while MTHFR A1298C AA genotype carriers displayed elevated comet assay units levels, implying intrinsic DNA damage (AA vs AC: 14.41±4.38 vs 7.89±5.54, p=0.04). Conclusions: The current report supports the contribution of MTHFR genetic variants in non-MALT NHL development in the setting of pSS, possibly through defective DNA methylation and repair mechanisms.